The effect of magnetic water treatment and KSC sulfacid fertigation in leaching salts soil efficiency - H. W. A., Al-jothery; D. J., Abdulsada (Al-Qadisiyah Journal of Pure Science, 2017)
Magnetic water technology has been tested to treat water quality and fertigation KSC sulfacid fertilizer to improve the efficiency of salts soil leaching, experiment a laboratory conducted to columns of soil placed in each column 1750g soil with tissues alluvial silt clay loam contained on (580 loam, 300 clay and 120 sand) g. Kg-1 soil at an average density of virtual amounted to 1.1 Mg. M-3 and the electrical conductivity of the extract (1:1) 78.3ds.M-1 and pH = 7.9. The experiment included ten leaches to soil columns with water electric conductivity 1.7ds.m-1, pH= 8.2 and equal amounts of two experiments, the first is completely randomized design (CRD) and the second is completely randomized blocks design (RCBD) and treatments consisted by control treatment (normal water leaching), magnetic water treatment and leaching by using KSC sulfacid fertilizer containing on sulfur (SO3) 41% and nitrogen (urea) 15% and by dilution 2 ml. L-1 and double leaching (magnetized water + KSC sulfacid fertilizer) with three Replicates. Conducted after every leaching electrical conductivity and interactive tested (EC and pH) to the soil filter respectively to the tenth and last leach after columns dry taken from a sample representative of each column and work it extract (1 soil: 1 water), and has conducted tests (EC and pH). Magnetic water treatment processed by using â€œBio Magnet Bi Polar System techniquesâ€ locally made (Iraq) strongly in 2000 gauss. Inch-1, discharge 1000 liters. h-1. Treated magnetically water, KSC sulfacid fertilizer and double leaching (magnetized water + KSC sulfacid fertilizer) show that in leaching process decrease significant in the values of electrical conductivity compared with normal water; The percentage of reduction is (28.80 and 36.00 and 58.00)%, respectively. Significantly increased recorded for soil interaction when the use of magnetic water treated, sulfur fertilizer dissolved in water and double leaching (magnetized water + KSC sulfacid fertilizer) in leaching process compared to using control water; as increase percentage is (0.38, 5.8 and 8.9)%, respectively, and the treatments have shown differences among them through the leaching curves of electrical conductivity and pH to ten leaching filter.